Traduction automatique des langues — espérances et enjeux des outils appliqués - Żłobińska-Nowak, Aleksandra (Neophilologica, 2013)
This paper deals with a short study of automatic translation and natural language processing in contemporary linguistics. The author presents the main reasons of their conception as well as their beginnings and expectations in the historical perspective. Also the difficulties in the domain of automatic translation like polysemy, ambiguity or choice of the formalisms appropriate to the description and the proposals of their resolution are focused on in the paper. In this context, the article examines the problem of word sense disambiguation according to the object oriented approach proposed by W. Banyś. The author seeks to demonstrate the differences in the choice of the linguistic means in French and Polish on the analyzed levels and the influence of occurrence in this description. The aim of this paper is also to indicate some possibilities to communicate our human linguistic abilities to the computer to ensure the correct machine translation.